PENGEMBANGAN INSTRUMEN ASESMEN KOMPETENSI MINIMUM (AKM) LITERASI MEMBACA DAN NUMERASI PADA MATERI STOIKIOMETRI - Niswah Zakiyyah, - (2022)
This study aims to produce a Minimum Competency Assessment (MCA) instrument on stoichiometric material that meets the test criteria that are appropriate to be used to measure reading literacy and numeracy of High School Students. The research method used is the method of development and validation. The participants involved in this study were five experts in the field of chemistry education as validators and 30 students of class XI in one of the high schools in Cimahi City as respondents. The product resulting from this research is the AKM instrument on stoichiometric material which consists of 7 reading literacy questions and 23 numeracy literacy questions with the form of the questions, namely 6 multiple choice questions, 9 complex multiple choice questions, 1 matching question, 8 short entry questions, and 6 questions. Essay Questions. All AKM items were declared valid based on content validity and based on empirical validity 29 valid questions and 1 invalid question. The results of the reliability test for the form of objective questions and descriptions were declared reliable with high criteria. The results of the item analysis when viewed from the level of difficulty, namely there are 9 easy questions, 20 moderate questions, and 1 difficult question, this is stated to have not met a good proportion of the difficulty level of the test. Judging from the distinguishing power test, the AKM questions developed have 2 questions with poor criteria, 4 questions with sufficient criteria, and 24 questions with very good criteria. Overall, the AKM instrument developed has good quality and is worthy of being used as an evaluation tool.